2017
DOI: 10.1164/rccm.201607-1408oc
|View full text |Cite
|
Sign up to set email alerts
|

Host–Microbial Interactions in Idiopathic Pulmonary Fibrosis

Abstract: Integrated analysis of the host transcriptome and microbial signatures demonstrated an apparent host response to the presence of an altered or more abundant microbiome. These responses remained elevated in longitudinal follow-up, suggesting that the bacterial communities of the lower airways may act as persistent stimuli for repetitive alveolar injury in IPF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
162
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(164 citation statements)
references
References 36 publications
2
162
0
Order By: Relevance
“…Unfortunately, there were no healthy controls in this study, but loss of diversity in IPF compare to healthy control was reported in a previous paper [13]. Also, Molyneaux PL et al suggested that the bacterial communities of the lower airways act as persistent stimuli for repetitive alveolar injury [19]. Taken together, loss of diversity might have some impact on the pathogenesis of IPF.…”
Section: Discussionmentioning
confidence: 51%
“…Unfortunately, there were no healthy controls in this study, but loss of diversity in IPF compare to healthy control was reported in a previous paper [13]. Also, Molyneaux PL et al suggested that the bacterial communities of the lower airways act as persistent stimuli for repetitive alveolar injury [19]. Taken together, loss of diversity might have some impact on the pathogenesis of IPF.…”
Section: Discussionmentioning
confidence: 51%
“…Other authors have recently tried to take a step forward in the understanding of the pathogenesis of IPF by assessing the interaction between the host and lung microbiota [29,30]. MOLYNEAUX et al [25] performed a longitudinal evaluation of host gene expression in peripheral blood cells from 60 IPF patients and 20 controls, from their prior contribution, and explored the potential association with BAL microbiota collected at baseline [29].…”
Section: Ipf and Host-microbiota Interactions And Potential Effects mentioning
confidence: 99%
“…MOLYNEAUX et al [25] performed a longitudinal evaluation of host gene expression in peripheral blood cells from 60 IPF patients and 20 controls, from their prior contribution, and explored the potential association with BAL microbiota collected at baseline [29]. In this preliminary study, the authors demonstrated that in IPF patients, when compared to controls, there were changes in the peripheral blood expression profile associated with the presence of an altered or more abundant microbiome.…”
Section: Ipf and Host-microbiota Interactions And Potential Effects mentioning
confidence: 99%
“…The study determined two operational taxonomic units (OTUs) associated with disease progression: Staphylococcus OTU 1348 and Streptococcus OTU 1345 [30]. This altered microbiome persists over time, which may implicate bacterial communities localised in the lower airways as persistent stimuli for repetitive alveolar injury in IPF [31]. IPF patients from the COMET cohort showed interactions between the host microbiome and progression-free survival [32].…”
Section: Microbiomementioning
confidence: 99%